Effect of electric field on exciton in high‐purity GaAs epilayer measured at room temperature. Issue 1 (1st January 2013) - Kayastha, M.S.; Sapkota, D.P.; Takahashi, M.; Wakita, K.
Abstract : The excitonic electroabsorption has been investigated for a high‐purity GaAs epilayer of 10 µm thickness at room temperature and clear red‐shift (≃1.44 nm) of the excitonic absorption peak has been observed. An extinction ratio over 10 dB has been obtained with an applied voltage of 11 V, which is nearly five times larger than the theoretical estimation without considering the exciton. This may be the first observation for of a surface normal structure with a polyaniline as a transparent Schottky electrode. The insertion loss is estimated to be 3 dB. This relative low driving voltage for a bulk configuration without quantum wells is due to high‐purity GaAs.